2021
DOI: 10.1002/cpp.2564
|View full text |Cite
|
Sign up to set email alerts
|

The influence of risk perception for COVID‐19 pandemic on posttraumatic stress disorder in healthcare workers: A survey from four designated hospitals

Abstract: The aim of current study was to investigate risk perception of COVID‐19 pandemic, sleep quality and time change of leisure activity and their correlations with posttraumatic stress disorder (PTSD) in healthcare workers (HCWs) from four designated hospitals in China. Medical staffs ( n = 317) from three designated hospitals in Guangdong Province and one designated hospital in Guangxi Province were surveyed on their demographic information, sleep quality and time change of leisure activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 52 publications
4
28
0
Order By: Relevance
“…For example, together with an acceptable time for recreational activity, a good sleep quality seems to protect from posttraumatic stress disorder a professional category heavily under pressure during the pandemic as the healthcare workers. 13 Put another way, sleep disturbances, on one hand, are related to the onset and worsening of psychiatric conditions and, on the other hand, represent the common consequence of exposure to traumatic events. 14 Interestingly, a study has found a significant indirect effect from exposure level to symptoms of post-traumatic stress via sleep quality in a sample of Chinese healthcare workers facing the COVID-19 pandemic at peak of the contagion.…”
Section: Introductionmentioning
confidence: 99%
“…For example, together with an acceptable time for recreational activity, a good sleep quality seems to protect from posttraumatic stress disorder a professional category heavily under pressure during the pandemic as the healthcare workers. 13 Put another way, sleep disturbances, on one hand, are related to the onset and worsening of psychiatric conditions and, on the other hand, represent the common consequence of exposure to traumatic events. 14 Interestingly, a study has found a significant indirect effect from exposure level to symptoms of post-traumatic stress via sleep quality in a sample of Chinese healthcare workers facing the COVID-19 pandemic at peak of the contagion.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the psychological impact of the epidemic on health care workers in different aspects, such as medical staff working in different risk workplace (15), different medical care population in front of this pandemic (16,17), and posttraumatic stress disorder symptoms (PTSD) (18,19). However, only a few studies have looked into the psychological stress during the first outbreak outside Wuhan, when a very limited knowledge of the disease existed.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers estimate the initial impact of the COVID-19 pandemic is a serious concern for our healthcare workers. Approximately 10% of healthcare workers self-reported symptoms of PTSD (Geng et al, 2021), a number likely underreported. As faculty, it may seem we do not have many options to help students who appear to have difficulty coping.…”
Section: Promoting Academic Integritymentioning
confidence: 99%